Evaluation of grasses for soil conservation - Patil, B D; Ghosh, Ranjit (Journal of Soil and Water Conservation, 2022)
Apart from their value in for- age production, grasses play an important role in the prevention of soil erosion and in the improvement of soil structure and fertility. In this context the study of the development of root system in various grasses assumes considerable importance. Relatively, very little work has been done in this country on this aspect but its importance has been adequately appreciated by soil conservationists. In the planning of the soil con- servation programme in the country naturally a great emphasis is laid on the use of grasses. During the last decade or so a number of grasses both exotic and indigenous wild are being tested by soil conserva- tion centres mainly for their adaptability under varied climatic and edaphic conditions prevailing in the country. As a result of this an appreciable working information is made available so far as the suitability of certain species for a particular region is concerned. As a subsequent step in the direction of soil conservation, it has, now, become necessary to recognize the various criteria for judging the relative merits and demerits of grasses for their value in betterment of soil. In evaluation studies on grasses for prevention of erosion and for improvement of soil, their root production, its distribution in different soil layers and its possible soil bind- ing action are the major factors that need to be looked into. In the present paper a report on the investigations carried out on the above factors in case of 24 gras- ses including some varieties that have shown promise under the semi- arid tract of north-west regions of the country is made.